2020
DOI: 10.15252/embr.202050662
|View full text |Cite
|
Sign up to set email alerts
|

FAM111 protease activity undermines cellular fitness and is amplified by gain‐of‐function mutations in human disease

Abstract: Dominant missense mutations in the human serine protease FAM111A underlie perinatally lethal gracile bone dysplasia and Kenny-Caffey syndrome, yet how FAM111A mutations lead to disease is not known. We show that FAM111A proteolytic activity suppresses DNA replication and transcription by displacing key effectors of these processes from chromatin, triggering rapid programmed cell death by Caspase-dependent apoptosis to potently undermine cell viability. Patient-associated point mutations in FAM111A exacerbate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(112 citation statements)
references
References 33 publications
8
100
0
Order By: Relevance
“…Together, our results demonstrate that FAM111A exhibits protease‐dependent cytotoxicity, which is amplified by the KCS2 and OCS patient mutants, consistent with recent studies (Kojima et al , 2020; Hoffmann et al , 2020). Thus, FAM111A hyperactivity can explain the dominant effects of FAM111A R569H and FAM111A S342del over wild‐type in the heterozygous disease state (Unger et al , 2013).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Together, our results demonstrate that FAM111A exhibits protease‐dependent cytotoxicity, which is amplified by the KCS2 and OCS patient mutants, consistent with recent studies (Kojima et al , 2020; Hoffmann et al , 2020). Thus, FAM111A hyperactivity can explain the dominant effects of FAM111A R569H and FAM111A S342del over wild‐type in the heterozygous disease state (Unger et al , 2013).…”
Section: Resultssupporting
confidence: 92%
“…Given that hyperactive FAM111A R569H disrupts cellular DNA replication, we envisioned that FAM111A could directly inhibit viral replication by degrading key replication factors. Crucially however, although others and we have identified replication factors as FAM111A interactors, to date none appear to be targets of its protease activity (Hoffmann et al , 2020). Instead, FAM111A causes nuclear barrier dysfunction, among other phenotypes, when SV40 HR mutants attempt to replicate in restrictive cells.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The fetus in this report shows phenotypic overlap with previously reported cases and the Y562S variant shares multiple similarities with previous reported pathogenic variants, including the well‐established pathogenic R569H mutation (Abraham et al, 2017; Isojima et al, 2014; Nikkel et al, 2014; Unger et al, 2013). Like the R569H variant, Y562S is a single nucleotide missense mutation resulting in a single amino acid change located in the C‐terminus, an evolutionarily conserved region of the protein that appears to be a hotspot for mutations (Abraham et al, 2017; Hoffmann et al, 2020; Isojima et al, 2014; Unger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Given this evidence, it has been theorized that FAM111A mutations cause phenotypic features by altering the protein's intermolecular interactions (Isojima et al, 2014; Unger et al, 2013). A recent study showed altered peptidase activity and gain of function mechanism as pathophysiology for FAM111A‐ related disorders (Hoffmann et al, 2020). Pathogenic mutations increased proteolytic activity of the protein resulting in decreased DNA replication and transcription ultimately resulting in programmed cell death (Hoffmann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%